The Impact Of Asset Structure, Liquidity, And Profitability On The Capital Structure Of Manufacturing Companies Listed On The Indonesia Stock Exchange - Erwin Febriansyah; Hilfa Mora Marito Nasution; Muliawati Muliawati; Calista Agnesia Ester (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of asset structure, liquidity, and profitability on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. Capital structure is measured using the Debt to Equity Ratio (DER), asset structure using the Fixed Asset Ratio (FAR), liquidity using the Current Ratio (CR), and profitability using Return on Assets (ROA). This research employs a quantitative approach using panel data from 20 manufacturing companies over four years (80 observations). The sampling technique used was random sampling. Panel data regression analysis was conducted using EViews 13. Based on the Chow and Hausman tests, the most appropriate model was the Fixed Effect Model. The results show that asset structure and liquidity have a positive and significant effect on capital structure, while profitability has a negative and significant effect. Simultaneously, asset structure, liquidity, and profitability significantly influence capital structure. The Adjusted R² value of 0.986 indicates that 98.6% of the variation in capital structure is explained by the three independent variables. These findings suggest that manufacturing firms with a high proportion of fixed assets and strong liquidity tend to use more debt, whereas highly profitable firms rely more on internal financing. This study provides insights for corporate management in determining optimal capital structure policies.